2019
DOI: 10.1002/ppap.201800213
|View full text |Cite
|
Sign up to set email alerts
|

One‐step deposition of nano‐Ag‐TiO2 coatings by atmospheric pressure plasma jet for water treatment: Application to trace pharmaceutical removal using solar photocatalysis

Abstract: In this study, micrometer thick Ag‐TiO2 coatings were deposited in a single and facile step by spraying the precursor in an atmospheric pressure plasma jet with different concentrations of Ag nanoparticles. The homogenous distribution of Ag decreased the TiO 2 crystal size and increased the surface area. The coatings were characterized to be porous with an anatase phase with improved charge separation and visible light absorption. The photocatalytic activity of the materials was investigated for degrading rhod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Considering that the calculated thin-film lengths using Equation (2) are in good agreement with the experimental data as shown in Figure 2, and the dusty cloud trapped by the plasma sheath, we performed a reasonable thin-film deposition process of atmospheric pressure pulse-modulated plasma (Figure 8). During plasma on, the TiO 2 particles are trapped by the plasma sheath, and they "drop" on the substrate when the plasma is off.…”
Section: Dynamic Study Of the Deposition Process In Modulated Rf Plasmasupporting
confidence: 58%
See 1 more Smart Citation
“…Considering that the calculated thin-film lengths using Equation (2) are in good agreement with the experimental data as shown in Figure 2, and the dusty cloud trapped by the plasma sheath, we performed a reasonable thin-film deposition process of atmospheric pressure pulse-modulated plasma (Figure 8). During plasma on, the TiO 2 particles are trapped by the plasma sheath, and they "drop" on the substrate when the plasma is off.…”
Section: Dynamic Study Of the Deposition Process In Modulated Rf Plasmasupporting
confidence: 58%
“…Anatase TiO 2 films have been well studied for their applications in electronic devices, [1] photocatalysts, [2,3] and solar cell development. [4,5] Lowtemperature, fast deposition of anatase TiO 2 films with a low cost will broaden applications such as flexible solar cells [6] and flexible sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Using this method, large photocatalytic activities were measured for coating from solutions with 0.3% and 0.4% Ag concentrations in TTIP. In this study, the authors concluded that pulse frequencies had a negligible effect on Rh.B degradation, whereas lower air flow rates induced a faster kinetics because such conditions caused higher crystallinity of the coating [112]. In general, the high porosity of APPJ-grown films was attributed to the high deposition rate and high kinetic energy of the reactive plasma species (i.e., radicals) generated and carried in the plasma jet.…”
Section: Atmospheric Pressure Dielectric Barrier Discharge Depositionmentioning
confidence: 99%
“…On the other hand, the PEC responses were superior for rf magnetron-sputtered deposited film [ 16 ]. Similarly, Rh.B was used to investigate the photocatalytic activity of nano-Ag–TiO 2 coatings deposited by APPJ ( Figure 9 ) [ 112 ]. By combining the APPJ with a spraying system, high deposition rates were achieved in the range of 10–20 μm/s.…”
Section: Atmospheric Pressure Plasma-enhanced Deposition Of Tio mentioning
confidence: 99%
See 1 more Smart Citation